Forecasting the Beef Meat Prices in Erbil Using Box-Jenkins Models - Feink Mohammed Omer; Wasfi Tahir Salih (Eurasian Journal of Management & Social Sciences)
Foodstuff has a crucial role for everybody life in the world. In Iraq, beef meat is one of the important parts of the food basket of every household in Erbil. Prices of beef meat fluctuates over time, according to the market prices and the economic situation in the country. The data used were averages of prices of beef meat were originally based on two observations each month took from (Kurdistan Regional Office of Statistics in Erbil city) for the period from January 2008 to December 2018. The methodology used for the forecasting was Box-Jenkins modelling. The best model achieved was ARIMA (0,2,2). Minimum value of Root Mean Square Error (RMSE), (MAE) and WK1 were used to select the best model.